Pengelolaan Vaksin, Penatalaksanaan Imunisasi Campak dan Efikasi Vaksin Campak di Kabupaten Sukoharjo - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT The Sukoharjo Regency has achieved UCI more than 3 years but the outbreak of measles is still occure in some areas. This research was aimed to know the vaccine management, the organization of measles immunization treatment and the large of measles vaccine efficacy. The research consisted of two phases, the first phase was to calculate the measles vaccine efficacy, by using the research design of cross sectional with population of batita (12-35 months old children). The sample size of 768 batitas were come from 30 Posyandus of 6 Puskesmas samples. The second research phase was a qualitative research by conducting an observation, a deep interview, and the structured group discussion to the vaccine managers and immunization vaccinators in Puskesmas and Posyandu in the first phase research location. The result showed that the vaccine efficacy was low which able to prevent the batita from measles that was 61.56% (95%, CI.40%-75%). The bad vaccine management, which was not fit to suggested provisions (refrigerator was oftenly opened, the unstandardized usage of cold pack and the volume